Coating material with high scratch resistance and wear resistance and preparation method thereof

By using specific components such as tetraphenol ethane tetraglycidyl ether epoxy resin, polyurethane modified polytetrafluoroethylene, acrylate modified polysilazane and modified nanotungsten carbide in the coating materials, the problem of poor adaptability of existing wear-resistant coating materials in different environments is solved, and high scratch resistance, wear resistance and corrosion resistance are improved.

CN119842293AInactive Publication Date: 2025-04-18NINGBO LIZHIYUAN STAMPING
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510154502.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing wear-resistant coating materials have poor adaptability and are easy to fall off under different environments. The wear-resistant performance decreases after long-term use, and cannot fully exert their wear resistance in high humidity, high temperature and other environments.

Method used

Through the combination of specific raw materials, a high scratch-resistant and wear-resistant coating material is prepared, including tetraphenol-based tetraglycidyl ether epoxy resin, polyurethane modified polytetrafluoroethylene, acrylate modified polysilazane, modified nanotungsten carbide, curing agent, dispersant and antioxidant. Through the combination and curing of these components, the scratch-resistant and wear-resistant properties of the coating are improved.

Benefits of technology

This coating material not only improves the scratch and wear resistance of the metal matrix, but also has good high temperature, high humidity and corrosion resistance. It has stable performance when used in different environments and meets the needs of various environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of coating materials, in particular to a high-scratch-resistant and wear-resistant coating material and a preparation method thereof.The high-scratch-resistant and wear-resistant coating material is prepared from, by weight, 20-30 parts of tetraphenol ethane tetraglycidyl ether epoxy resin, 15-25 parts of polyurethane modified polytetrafluoroethylene, 15-25 parts of acrylate modified polysilazane and 5-15 parts of modified nano tungsten carbide. 2-5 parts of a curing agent, 1-3 parts of a dispersing agent and 0.5-1 part of an antioxidant; the preparation method comprises the steps of raw material mixing, stirring, coating, drying, heat treatment and the like. Through matching of specific raw materials, the prepared coating paint not only can improve the scratch resistance and wear resistance of a metal matrix, but also has good high temperature resistance, high humidity resistance and corrosion resistance, and the performance is not affected when the coating paint is used in different environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of coating materials, and in particular to a highly scratch-resistant and wear-resistant coating material and a preparation method thereof. Background Art

[0002] Coating material is a material used to form a protective or functional film on the surface of a substrate. Depending on the type of raw materials, it can be divided into organic coating materials, inorganic coating materials, and composite coating materials. Common substrate materials include metal, plastic, and wood, among which metal is particularly widely used in the industrial field.

[0003] Coating a coating material with high hardness and high wear resistance on the surface of a metal substrate can protect the metal substrate from corrosion, reduce wear on the surface of the metal substrate, and increase the service life of the metal substrate.

[0004] However, existing wear-resistant coating materials have poor adaptability to different environments. They are easy to fall off due to weak bonding force under the influence of high-speed friction, heavy-load impact or mechanical stress. After long-term use, their wear resistance is easily reduced due to aging or corrosion. They are also unable to fully exert their wear resistance in high humidity, high temperature and other environments, and cannot meet the needs of adapting to various environments. Summary of the invention

[0005] The present application aims to overcome at least one of the defects of the prior art and provide a highly scratch-resistant and wear-resistant coating material and a preparation method thereof. By matching specific raw materials, the prepared coating material can not only improve the scratch resistance and wear resistance of the metal substrate, but also has good high temperature resistance, high humidity and corrosion resistance, and the performance is not affected when used in different environments.

[0006] In the first aspect, the embodiments of the present application provide a highly scratch-resistant and wear-resistant coating material, which is achieved through the following technical solutions: A highly scratch-resistant and wear-resistant coating material, comprising the following raw materials in parts by weight: 20-30 parts of tetraphenol ethane tetraglycidyl ether epoxy resin, 15-25 parts of polyurethane modified polytetrafluoroethylene, 15-25 parts of acrylate modified polysilazane, 5-15 parts of modified nano tungsten carbide, 2-5 parts of curing agent, 1-3 parts of dispersant, and 0.5-1 part of antioxidant.

[0007] The highly scratch-resistant and wear-resistant coating material according to the embodiment of the present application has at least the following beneficial effects: The high scratch-resistant and wear-resistant coating material of the present application is prepared by selecting different components. The epoxy resin has strong corrosion resistance, wear resistance and adhesion, polytetrafluoroethylene has good wear resistance and excellent chemical stability, and polysilazane has good high temperature resistance and corrosion resistance. By combining a variety of organic substances and filling modified nano-tungsten carbide into the gaps in the composite coating, the coating is cross-linked and cured with a curing agent to further improve the scratch resistance and wear resistance of the coating, and improve the strength and stability of the coating.

[0008] Ordinary epoxy resins have the disadvantages of being brittle, having poor fatigue resistance and impact toughness, and are difficult to meet the corrosion resistance requirements in specific application environments. The tetraphenol ethane tetraglycidyl ether epoxy resin of the present application contains four epoxy groups, has high functionality, and has a high cross-linking density of the coating after curing, which can improve the strength, corrosion resistance, and high temperature resistance of the coating.

[0009] Polysilazane has good high temperature resistance and corrosion resistance, and can maintain stable performance in high temperature environments without decomposition or shedding. The corrosion resistance and weather resistance of polysilazane modified by acrylate are further improved, and it can adapt to more environments. At the same time, it improves the bonding strength with metal substrates and other raw materials, and improves the stability of coating materials in different environments.

[0010] Polytetrafluoroethylene has good wear resistance and excellent chemical stability. The elasticity and adhesion of polyurethane and the good wear resistance and high and low temperature resistance of polytetrafluoroethylene are combined by polyurethane modified polytetrafluoroethylene. Polyurethane modified polytetrafluoroethylene not only has excellent wear resistance and high and low temperature resistance, but also has good elasticity and adhesion. It can maintain stability and is not easy to fall off when subjected to external force impact.

[0011] Tungsten carbide has high hardness and corrosion resistance. Nano-tungsten carbide in the coating can improve the hardness and wear resistance of the coating, and enhance the oxidation resistance and corrosion resistance of the coating.

[0012] Poor dispersibility will affect the uniform distribution of raw materials, resulting in uneven coating surface. The dispersant of the present application can improve the dispersion coefficient of raw materials, make the distribution of modified nano-tungsten carbide and resin and other raw materials more uniform, and match each other to enhance the hardness and oxidation resistance of highly scratch-resistant and wear-resistant coating materials.

[0013] According to some embodiments of the present application, the preparation of the polyurethane modified polytetrafluoroethylene includes the following steps: dehydrating 8-12 parts of trihydroxy polyoxypropylene ether by weight at a temperature of 100-120°C and a vacuum degree of -0.1MPa for 1-2h; cooling to 60-80°C, adding 6-8 parts of hexamethylene diisocyanate, and reacting at 78-82°C for 1.5-2h to synthesize a prepolymer; adding 5-10 parts of polytetrafluoroethylene, 0.02-0.04 parts of a catalyst, 2-3 parts of 4,4'-methylenebis(2-chloroaniline), and 8-15 parts of a solvent, heating to 110-120°C and mixing evenly to obtain polyurethane modified polytetrafluoroethylene.

[0014] Furthermore, the solvent is a mixture of methyl butyl ketone and toluene in a weight ratio of 1:(1-2).

[0015] Furthermore, the catalyst includes at least one of dibutyltin diacetate, stannous octoate, dibutyltin dilaurate, and bismuth laurate.

[0016] According to some embodiments of the present application, the preparation of the acrylate-modified polysilazane comprises the following steps: S1. Dissolve 6-8 parts of 3-(trimethyloxysilyl)propyl methacrylate and 0.1-0.2 parts of dimethylaminopyridine in an organic solvent according to weight parts, and adjust the pH value to 4-6 to obtain an acrylate mixture; S2. Dissolve 5-6 parts of polysilazane in an organic solvent according to weight to obtain a polysilazane mixed solution, add the acrylate mixed solution dropwise to the polysilazane mixed solution at a rate of 1-6 drops / second, mix well, remove the organic solvent after the reaction, add 0.1-0.2 parts of a photoinitiator, and obtain acrylate-modified polysilazane.

[0017] Due to the nucleophilicity and small steric hindrance of amino ions, dimethylaminopyridine can ensure that the Si-N of the polysilazane main chain is continuous, reduce the activation energy of the reaction, activate the Si-H group, and make the reaction easier to proceed. It can not only connect the polysilazane side chain with the modifier, but also promote the dehydrogenation coupling reaction between polysilazanes to increase the molecular weight.

[0018] Furthermore, the photoinitiator in step S2 is selected from at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, (2,4,6-trimethylbenzoyl)diphenylphosphine oxide and 2-isopropylthioxanthone.

[0019] Furthermore, the organic solvents in step S1 and step S2 are each independently selected from at least one of benzene, toluene, xylene, pentane, hexane, octane, cyclohexane, cyclohexanone, acetone, methyl butyl ketone, ethanol, and isopropanol.

[0020] According to some embodiments of the present application, the preparation of the modified nano-tungsten carbide comprises the following steps: A1. Ultrasonic dispersion of nano-tungsten carbide in a mixed solution of anhydrous ethanol and deionized water (8-9):1 by mass ratio, and adding N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane under stirring, raising the temperature to 70-80°C, constant temperature magnetic stirring for 5-8h, centrifugation, washing, and drying to obtain organosilicon-modified nano-tungsten carbide; A2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4 hours, and dried and ground after the reaction is completed; A3. Add the graphene pretreated in step A2 to ethanol for ultrasonic dispersion, add the organosilicon-modified nano-tungsten carbide prepared in step A1, stir rapidly at 25-35°C to allow it to react fully, centrifuge, wash several times with anhydrous ethanol, dry in vacuum, and grind to obtain modified nano-tungsten carbide.

[0021] Modified nano tungsten carbide is used as filler in highly scratch-resistant and wear-resistant coating materials. Nano materials can enhance the mechanical properties of coating materials due to their large specific surface area and high adsorption performance; tungsten carbide can effectively improve wear resistance and corrosion resistance; silicone can increase the dispersion of nano tungsten carbide in coating materials, improve the elasticity, wear resistance and corrosion resistance of coating materials; after graphene is acidified, the surface will be oxidized into carboxyl groups, which will combine with silicone-modified nano tungsten carbide, reducing the problem of easy agglomeration of graphene. The layered structure of graphene makes the mixing between filler and resin more complete, improving the high temperature resistance and tensile strength of coating materials.

[0022] Furthermore, in step A1, the weight ratio of the nano-tungsten carbide, the anhydrous ethanol and the N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane is 1:(8-10):(0.1-0.2).

[0023] According to some embodiments of the present application, the dispersant includes carbamate and polycarboxylate. Carbamate can help maintain and enhance the dispersion state of the raw materials, has excellent dispersibility and anti-precipitation properties, can achieve good dispersion effects at very low dosages, and can also improve the wettability of the modified nano-tungsten carbide, thereby improving the adhesion and durability of the coating; polycarboxylate has excellent dispersion performance and stability, can achieve good dispersion effects at low concentrations, and can effectively reduce the viscosity and stickiness of the coating, and improve the leveling of the coating; the combination of the two can improve the bonding strength of the coating and enhance scratch resistance and wear resistance.

[0024] According to some embodiments of the present application, the curing agent is formed by mixing triethylenetetramine and hydroxyalkylamide curing agent in a weight ratio of (1-2):1.

[0025] According to some embodiments of the present application, the antioxidant is selected from at least one of 2,6-di-tert-butyl-p-cresol, tert-butylhydroquinone, butylated hydroxyanisole, hydroquinone or o-methylhydroquinone. The antioxidant in the present application can increase the storage time of the coating, maintain the activity of the groups in the coating, and improve the curing effect of the coating.

[0026] In a second aspect, the present application provides a method for preparing the above-mentioned highly scratch-resistant and wear-resistant coating material, which is achieved by the following technical solutions: The method for preparing the above-mentioned highly scratch-resistant and wear-resistant coating material comprises the following steps: (1) Tetraphenol ethane tetraglycidyl ether epoxy resin, polyurethane modified polytetrafluoroethylene, acrylate modified polysilazane, modified nano tungsten carbide and dispersant are stirred and mixed according to weight parts for 3-4 minutes at a stirring temperature of 15-25° C. to obtain a mixed raw material; (2) Add the curing agent to the mixed raw materials according to the weight portion and stir for 8-10 minutes at a stirring temperature of 40-50° C. to obtain a mixed coating; (3) adding an antioxidant to the mixed coating according to parts by weight and stirring for 5-6 minutes at a stirring temperature of 15-25° C. to obtain an antioxidant coating; (4) The antioxidant coating is applied to the surface of a metal substrate, first dried, and then heat treated to obtain a highly scratch-resistant and wear-resistant coating material.

[0027] The method for preparing a highly scratch-resistant and wear-resistant coating material according to the embodiment of the present application has at least the following beneficial effects: The preparation method of the present application has simple steps, does not require the use of complex production equipment, has low cost, is pollution-free during the manufacturing process, does not emit toxic substances, does not harm the health of operators, and is suitable for industrial production.

[0028] The present application performs a drying treatment in advance, which helps to absorb the organic solvent in the antioxidant coating, thereby reducing the particle agglomeration phenomenon caused by the surface tension of the organic solvent inside the coating, thereby making the raw materials more evenly dispersed; drying allows the cross-linking between the resins to proceed gradually, which has a certain impact on the hardness and scratch resistance of the prepared coating.

[0029] According to some embodiments of the present application, the drying in step (4) includes pre-drying and post-drying.

[0030] Furthermore, the pre-drying temperature is 115-140°C.

[0031] Furthermore, the pre-drying time is 20-30 minutes.

[0032] Furthermore, the post-drying temperature is 150-170°C.

[0033] Furthermore, the drying time of the post-drying is 25-35 minutes.

[0034] According to some embodiments of the present application, the drying method in step (4) is hot air drying.

[0035] According to some embodiments of the present application, the temperature of the heat treatment in step (4) is 210-240°C.

[0036] According to some embodiments of the present application, the heat treatment time in step (4) is 10-15 hours.

[0037] According to some embodiments of the present application, the heat treatment in step (4) is performed by drying under constant temperature and humidity conditions, wherein the relative humidity is 25%-35%.

[0038] The specific drying and heat treatment process of the present application can effectively improve the coating hardness and scratch resistance of the metal substrate. After treatment at different temperatures and times, the cross-linking reaction of each raw material in the coating can be more complete. DETAILED DESCRIPTION

[0039] To make the purpose, technical solution and advantages of the present application clearer, the following will be further described in detail in conjunction with specific embodiments. The embodiments described here are only part of the embodiments of the present application and cannot be understood as limiting the scope of protection of the present application.

[0040] Example 1

[0041] Preparation of highly scratch-resistant and wear-resistant coating materials: Select the following raw materials by weight: 25 parts of tetraphenol ethane tetraglycidyl ether epoxy resin, 20 parts of polyurethane-modified polytetrafluoroethylene, 20 parts of acrylate-modified polysilazane, 10 parts of modified nano-tungsten carbide, 4 parts of curing agent, 2 parts of dispersant, and 0.8 parts of 2,6-di-tert-butyl-p-cresol; wherein the dispersant includes carbamate and polycarboxylate ether, and the curing agent is a mixture of triethylenetetramine and hydroxyalkylamide curing agent in a weight ratio of 1.5:1; (1) tetraphenol ethane tetraglycidyl ether epoxy resin, polyurethane modified polytetrafluoroethylene, acrylate modified polysilazane, modified nano tungsten carbide and dispersant were stirred and mixed according to weight parts for 4 minutes at a stirring temperature of 20° C. to obtain a mixed raw material; (2) Adding the curing agent to the mixed raw materials according to the weight portion and stirring for 9 minutes at a stirring temperature of 45° C. to obtain a mixed coating; (3) Adding 2,6-di-tert-butyl-p-cresol into the mixed coating according to parts by weight and stirring for 6 minutes at a stirring temperature of 20° C. to obtain an antioxidant coating; (4) applying the antioxidant coating to the surface of the metal substrate, first pre-drying at a temperature of 125° C. for 25 minutes, then post-drying at a temperature of 160° C. for 30 minutes, both pre-drying and post-drying are performed by hot air drying, and then heat treatment is performed at a temperature of 230° C. for 13 hours, the heat treatment method is drying under constant temperature and humidity conditions, wherein the relative humidity is 30%, to obtain a highly scratch-resistant and wear-resistant coating material; The preparation method of polyurethane modified polytetrafluoroethylene is as follows: dehydrate 10 parts of trihydroxy polyoxypropyl ether by weight at a temperature of 110°C and a vacuum degree of -0.1MPa for 1.5 hours; cool to 70°C, add 7 parts of hexamethylene diisocyanate, and react at 80°C for 1.8 hours to synthesize a prepolymer; add 8 parts of polytetrafluoroethylene, 0.03 parts of dibutyltin dilaurate, 2.5 parts of 4,4'-methylenebis(2-chloroaniline), and 12 parts of a solvent, heat to 115°C and mix evenly to obtain polyurethane modified polytetrafluoroethylene; The solvent is a mixture of methyl butyl ketone and toluene in a weight ratio of 1:1.5; The preparation of acrylate-modified polysilazane comprises the following steps: S1. Dissolve 7 parts of 3-(trimethyloxysilyl)propyl methacrylate and 0.15 parts of dimethylaminopyridine in isopropanol according to weight, and adjust the pH value to 4-6 to obtain an acrylate mixture; S2. Dissolve 6 parts of polysilazane in cyclohexane according to weight to obtain a polysilazane mixed solution, add the acrylate mixed solution dropwise to the polysilazane mixed solution at a rate of 4 drops / second, mix evenly, remove the organic solvent after the reaction, add 0.2 parts of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, and obtain acrylate-modified polysilazane; The preparation of modified nano-tungsten carbide includes the following steps: A1. Ultrasonic dispersion of nano-tungsten carbide in a mixed solution of anhydrous ethanol and deionized water in a mass ratio of 8.5:1, and adding N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane under stirring, raising the temperature to 75°C, constant temperature magnetic stirring for 7 hours, centrifugation, washing, and drying to obtain organosilicon-modified nano-tungsten carbide; A2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4 hours, and dried and ground after the reaction is completed; A3. The graphene pretreated in step A2 is added to ethanol for ultrasonic dispersion, and the organosilicon-modified nano-tungsten carbide prepared in step A1 is added, and the mixture is rapidly stirred at 30°C for full reaction, centrifuged, washed several times with anhydrous ethanol, and then vacuum dried, and ground to obtain modified nano-tungsten carbide; In step A1, the weight ratio of the nano-tungsten carbide, the anhydrous ethanol and the N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane is 1:9:0.2.

[0042] Example 2

[0043] Preparation of highly scratch-resistant and wear-resistant coating materials: Select the following raw materials by weight: 30 parts of tetraphenol ethane tetraglycidyl ether epoxy resin, 15 parts of polyurethane-modified polytetrafluoroethylene, 25 parts of acrylate-modified polysilazane, 5 parts of modified nano-tungsten carbide, 5 parts of curing agent, 1 part of dispersant, and 1 part of butylated hydroxyanisole; wherein the dispersant includes carbamate and polycarboxylate ether, and the curing agent is a mixture of triethylenetetramine and hydroxyalkylamide curing agent in a weight ratio of 1:1; (1) tetraphenol ethane tetraglycidyl ether epoxy resin, polyurethane modified polytetrafluoroethylene, acrylate modified polysilazane, modified nano tungsten carbide, and a dispersant were stirred and mixed according to weight parts for 4 minutes at a stirring temperature of 15° C. to obtain a mixed raw material; (2) Adding the curing agent to the mixed raw materials according to the weight portion and stirring for 10 minutes at a stirring temperature of 40° C. to obtain a mixed coating; (3) adding butylated hydroxyanisole to the mixed coating according to parts by weight and stirring for 6 minutes at a stirring temperature of 15° C. to obtain an antioxidant coating; (4) applying the antioxidant coating to the surface of the metal substrate, first pre-drying at a temperature of 140° C. for 20 minutes, and then post-drying at a temperature of 170° C. for 25 minutes, both pre-drying and post-drying are performed by hot air drying, and then heat treatment is performed at a temperature of 240° C. for 10 hours, and the heat treatment method is drying under constant temperature and humidity conditions, wherein the relative humidity is 35%, to obtain a highly scratch-resistant and wear-resistant coating material; The preparation method of polyurethane modified polytetrafluoroethylene is as follows: dehydrate 8 parts of trihydroxy polyoxypropylene ether by weight at a temperature of 120°C and a vacuum degree of -0.1MPa for 1 hour; cool to 80°C, add 6 parts of hexamethylene diisocyanate, and react at 82°C for 1.5 hours to synthesize a prepolymer; add 10 parts of polytetrafluoroethylene, 0.02 parts of stannous octoate, 3 parts of 4,4'-methylenebis(2-chloroaniline), and 8 parts of a solvent, heat to 120°C and mix evenly to obtain polyurethane modified polytetrafluoroethylene; The solvent is a mixture of methyl butyl ketone and toluene in a weight ratio of 1:1; The preparation of acrylate-modified polysilazane comprises the following steps: S1. 8 parts by weight of 3-(trimethyloxysilyl)propyl methacrylate and 0.1 parts of dimethylaminopyridine were dissolved in ethanol and the pH value was adjusted to 4-6 to obtain an acrylate mixture; S2. Dissolving 6 parts of polysilazane in hexane to obtain a polysilazane mixture according to parts by weight, adding the acrylate mixture dropwise to the polysilazane mixture at a rate of 1 drop / second, mixing evenly, removing the organic solvent after the reaction, adding 0.2 parts of 2-isopropylthioxanthone to obtain an acrylate-modified polysilazane; The preparation of modified nano-tungsten carbide includes the following steps: A1. Ultrasonic dispersion of nano-tungsten carbide in a mixed solution of anhydrous ethanol and deionized water in a mass ratio of 8:1, and adding N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane under stirring, raising the temperature to 80°C, and magnetic stirring at constant temperature for 5 hours, and obtaining organosilicon-modified nano-tungsten carbide after centrifugation, washing and drying; A2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4 hours, and dried and ground after the reaction is completed; A3. The graphene pretreated in step A2 is added to ethanol for ultrasonic dispersion, and the organosilicon-modified nano-tungsten carbide prepared in step A1 is added, and the mixture is rapidly stirred at 35°C to fully react, centrifuged, washed several times with anhydrous ethanol, and then vacuum dried, and ground to obtain modified nano-tungsten carbide; In step A1, the weight ratio of the nano-tungsten carbide, the anhydrous ethanol and the N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane is 1:8:0.2.

[0044] Example 3

[0045] Preparation of highly scratch-resistant and wear-resistant coating materials: Select the following raw materials by weight: 20 parts of tetraphenol ethane tetraglycidyl ether epoxy resin, 25 parts of polyurethane-modified polytetrafluoroethylene, 15 parts of acrylate-modified polysilazane, 15 parts of modified nano-tungsten carbide, 2 parts of curing agent, 3 parts of dispersant, and 0.5 parts of o-methyl hydroquinone; wherein the dispersant includes carbamate and polycarboxylate ether, and the curing agent is a mixture of triethylenetetramine and hydroxyalkylamide curing agent in a weight ratio of 2:1; (1) tetraphenol ethane tetraglycidyl ether epoxy resin, polyurethane modified polytetrafluoroethylene, acrylate modified polysilazane, modified nano tungsten carbide and dispersant were stirred and mixed according to weight parts for 3 minutes at a stirring temperature of 25° C. to obtain a mixed raw material; (2) Adding the curing agent to the mixed raw materials according to the weight portion and stirring for 8 minutes at a stirring temperature of 50° C. to obtain a mixed coating; (3) adding o-methyl hydroquinone to the mixed coating according to parts by weight and stirring for 5 minutes at a stirring temperature of 25° C. to obtain an antioxidant coating; (4) applying the antioxidant coating to the surface of the metal substrate, first pre-drying at a temperature of 115° C. for 30 minutes, and then post-drying at a temperature of 150° C. for 35 minutes, both pre-drying and post-drying are performed by hot air drying, and then heat treatment is performed at a temperature of 210° C. for 15 hours, and the heat treatment method is drying under constant temperature and humidity conditions, wherein the relative humidity is 25%, to obtain a highly scratch-resistant and wear-resistant coating material; The preparation method of polyurethane modified polytetrafluoroethylene is as follows: dehydrate 12 parts of trihydroxy polyoxypropyl ether by weight at a temperature of 100°C and a vacuum degree of -0.1MPa for 2 hours; cool to 60°C, add 8 parts of hexamethylene diisocyanate, and react at 78°C for 2 hours to synthesize a prepolymer; add 5 parts of polytetrafluoroethylene, 0.04 parts of bismuth laurate, 2 parts of 4,4'-methylenebis(2-chloroaniline), and 15 parts of a solvent, heat to 110°C and mix evenly to obtain polyurethane modified polytetrafluoroethylene; The solvent is a mixture of methyl butyl ketone and toluene in a weight ratio of 1:2; The preparation of acrylate-modified polysilazane comprises the following steps: S1. 6 parts by weight of 3-(trimethyloxysilyl)propyl methacrylate and 0.2 parts of dimethylaminopyridine were dissolved in methyl butyl ketone and the pH value was adjusted to 4-6 to obtain an acrylate mixture; S2. Dissolve 5 parts of polysilazane in xylene according to weight to obtain a polysilazane mixed solution, add the acrylate mixed solution dropwise to the polysilazane mixed solution at a rate of 6 drops / second, mix evenly, remove the organic solvent after the reaction, add 0.1 parts of (2,4,6-trimethylbenzoyl) diphenylphosphine oxide, and obtain acrylate-modified polysilazane; The preparation of modified nano-tungsten carbide includes the following steps: A1. Ultrasonic dispersion of nano-tungsten carbide in a mixed solution of anhydrous ethanol and deionized water in a mass ratio of 9:1, and adding N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane under stirring, raising the temperature to 70°C, and magnetic stirring at constant temperature for 8 hours, and obtaining organosilicon-modified nano-tungsten carbide after centrifugation, washing and drying; A2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4 hours, and dried and ground after the reaction is completed; A3. The graphene pretreated in step A2 is added to ethanol for ultrasonic dispersion, and the organosilicon-modified nano-tungsten carbide prepared in step A1 is added, and the mixture is rapidly stirred at 25°C for full reaction, centrifuged, washed several times with anhydrous ethanol, and then vacuum dried, and ground to obtain modified nano-tungsten carbide; In step A1, the weight ratio of the nano-tungsten carbide, the anhydrous ethanol and the N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane is 1:10:0.1.

[0046] Example 4

[0047] Preparation of highly scratch-resistant and wear-resistant coating materials: Select the following raw materials by weight: 26 parts of tetraphenol ethane tetraglycidyl ether epoxy resin, 20 parts of polyurethane-modified polytetrafluoroethylene, 18 parts of acrylate-modified polysilazane, 10 parts of modified nano-tungsten carbide, 3 parts of curing agent, 2 parts of dispersant, and 0.7 parts of hydroquinone; wherein the dispersant includes carbamate and polycarboxylate ether, and the curing agent is a mixture of triethylenetetramine and hydroxyalkylamide curing agent in a weight ratio of 2:1; (1) Tetraphenol ethane tetraglycidyl ether epoxy resin, polyurethane modified polytetrafluoroethylene, acrylate modified polysilazane, modified nano tungsten carbide and dispersant are stirred and mixed according to weight parts for 3-4 minutes at a stirring temperature of 15-25° C. to obtain a mixed raw material; (2) Add the curing agent to the mixed raw materials according to the weight portion and stir for 8-10 minutes at a stirring temperature of 40-50° C. to obtain a mixed coating; (3) adding hydroquinone to the mixed coating according to parts by weight and stirring for 5-6 minutes at a stirring temperature of 15-25° C. to obtain an antioxidant coating; (4) applying the antioxidant coating to the surface of the metal substrate, first pre-drying at a temperature of 115-140° C. for 20-30 minutes, and then post-drying at a temperature of 150-170° C. for 25-35 minutes, both pre-drying and post-drying are performed by hot air drying, and then heat treatment is performed at a temperature of 210-240° C. for 10-15 hours, and the heat treatment method is drying under constant temperature and humidity conditions, wherein the relative humidity is 25%-35%, to obtain a highly scratch-resistant and wear-resistant coating material; The preparation method of polyurethane modified polytetrafluoroethylene is as follows: dehydrate 8-12 parts of trihydroxy polyoxypropyl ether by weight at a temperature of 100-120°C and a vacuum degree of -0.1MPa for 1-2h; cool to 60-80°C, add 6-8 parts of hexamethylene diisocyanate, and react at 78-82°C for 1.5-2h to synthesize a prepolymer; add 5-10 parts of polytetrafluoroethylene, 0.02-0.04 parts of dibutyltin diacetate, 2-3 parts of 4,4'-methylenebis(2-chloroaniline), and 8-15 parts of a solvent, heat to 110-120°C, and mix evenly to obtain polyurethane modified polytetrafluoroethylene; The solvent is a mixture of methyl butyl ketone and toluene in a weight ratio of 1:(1-2); The preparation of acrylate-modified polysilazane comprises the following steps: S1. Dissolve 6-8 parts of 3-(trimethyloxysilyl)propyl methacrylate and 0.1-0.2 parts of dimethylaminopyridine in cyclohexanone according to weight parts, adjust the pH value to 4-6, and obtain an acrylate mixture; S2. Dissolve 5-6 parts of polysilazane in isopropanol according to weight to obtain a polysilazane mixture, add the acrylate mixture dropwise to the polysilazane mixture at a rate of 1-6 drops / second, mix well, remove the organic solvent after the reaction, add 0.1-0.2 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone, and obtain acrylate-modified polysilazane; The preparation of modified nano-tungsten carbide includes the following steps: A1. Ultrasonic dispersion of nano-tungsten carbide in a mixed solution of anhydrous ethanol and deionized water (8-9):1 by mass ratio, and adding N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane under stirring, raising the temperature to 70-80°C, constant temperature magnetic stirring for 5-8h, centrifugation, washing, and drying to obtain organosilicon-modified nano-tungsten carbide; A2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4 hours, and dried and ground after the reaction is completed; A3. The graphene pretreated in step A2 is added to ethanol for ultrasonic dispersion, and the organosilicon-modified nano-tungsten carbide prepared in step A1 is added, and the mixture is rapidly stirred at 25-35°C to fully react, centrifuged, washed several times with anhydrous ethanol, and then vacuum dried, and ground to obtain modified nano-tungsten carbide; In step A1, the weight ratio of the nano-tungsten carbide, the anhydrous ethanol and the N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane is 1:(8-10):(0.1-0.2).

[0048] Comparative Example 1 Preparation of highly scratch-resistant and wear-resistant coating materials: Select the following raw materials by weight: 25 parts of tetraphenol ethane tetraglycidyl ether epoxy resin, 20 parts of polyurethane-modified polytetrafluoroethylene, 20 parts of polysilazane, 10 parts of modified nano-tungsten carbide, 4 parts of curing agent, 2 parts of dispersant, and 0.8 parts of 2,6-di-tert-butyl-p-cresol; wherein the dispersant includes carbamate and polycarboxylate ether, and the curing agent is a mixture of triethylenetetramine and hydroxyalkylamide curing agent in a weight ratio of 1.5:1; (1) Tetraphenol ethane tetraglycidyl ether epoxy resin, polyurethane modified polytetrafluoroethylene, polysilazane, modified nano tungsten carbide, and a dispersant were stirred and mixed according to weight parts for 4 minutes at a stirring temperature of 20° C. to obtain a mixed raw material; (2) Adding the curing agent to the mixed raw materials according to the weight portion and stirring for 9 minutes at a stirring temperature of 45° C. to obtain a mixed coating; (3) Adding 2,6-di-tert-butyl-p-cresol into the mixed coating according to parts by weight and stirring for 6 minutes at a stirring temperature of 20° C. to obtain an antioxidant coating; (4) applying the antioxidant coating to the surface of the metal substrate, first pre-drying at a temperature of 125° C. for 25 minutes, then post-drying at a temperature of 160° C. for 30 minutes, both pre-drying and post-drying are performed by hot air drying, and then heat treatment is performed at a temperature of 230° C. for 13 hours, the heat treatment method is drying under constant temperature and humidity conditions, wherein the relative humidity is 30%, to obtain a highly scratch-resistant and wear-resistant coating material; The preparation method of polyurethane modified polytetrafluoroethylene is as follows: dehydrate 10 parts of trihydroxy polyoxypropyl ether by weight at a temperature of 110°C and a vacuum degree of -0.1MPa for 1.5 hours; cool to 70°C, add 7 parts of hexamethylene diisocyanate, and react at 80°C for 1.8 hours to synthesize a prepolymer; add 8 parts of polytetrafluoroethylene, 0.03 parts of dibutyltin dilaurate, 2.5 parts of 4,4'-methylenebis(2-chloroaniline), and 12 parts of a solvent, heat to 115°C and mix evenly to obtain polyurethane modified polytetrafluoroethylene; The solvent is a mixture of methyl butyl ketone and toluene in a weight ratio of 1:1.5; The preparation of modified nano-tungsten carbide includes the following steps: A1. Ultrasonic dispersion of nano-tungsten carbide in a mixed solution of anhydrous ethanol and deionized water in a mass ratio of 8.5:1, and adding N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane under stirring, raising the temperature to 75°C, constant temperature magnetic stirring for 7 hours, centrifugation, washing, and drying to obtain organosilicon-modified nano-tungsten carbide; A2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4 hours, and dried and ground after the reaction is completed; A3. The graphene pretreated in step A2 is added to ethanol for ultrasonic dispersion, and the organosilicon-modified nano-tungsten carbide prepared in step A1 is added, and the mixture is rapidly stirred at 30°C for full reaction, centrifuged, washed several times with anhydrous ethanol, and then vacuum dried, and ground to obtain modified nano-tungsten carbide; In step A1, the weight ratio of the nano-tungsten carbide, the anhydrous ethanol and the N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane is 1:9:0.2.

[0049] Comparative Example 2 Preparation of highly scratch-resistant and wear-resistant coating materials: Select the following raw materials by weight: 25 parts of tetraphenol ethane tetraglycidyl ether epoxy resin, 20 parts of polytetrafluoroethylene, 20 parts of acrylate-modified polysilazane, 10 parts of modified nano-tungsten carbide, 4 parts of curing agent, 2 parts of dispersant, and 0.8 parts of 2,6-di-tert-butyl-p-cresol; wherein the dispersant includes carbamate and polycarboxylate ether, and the curing agent is a mixture of triethylenetetramine and hydroxyalkylamide curing agent in a weight ratio of 1.5:1; (1) Tetraphenol ethane tetraglycidyl ether epoxy resin, polytetrafluoroethylene, acrylate-modified polysilazane, modified nano-tungsten carbide, and a dispersant were stirred and mixed according to weight parts for 4 minutes at a stirring temperature of 20° C. to obtain a mixed raw material; (2) Adding the curing agent to the mixed raw materials according to the weight portion and stirring for 9 minutes at a stirring temperature of 45° C. to obtain a mixed coating; (3) Adding 2,6-di-tert-butyl-p-cresol into the mixed coating according to parts by weight and stirring for 6 minutes at a stirring temperature of 20° C. to obtain an antioxidant coating; (4) applying the antioxidant coating to the surface of the metal substrate, first pre-drying at a temperature of 125° C. for 25 minutes, then post-drying at a temperature of 160° C. for 30 minutes, both pre-drying and post-drying are performed by hot air drying, and then heat treatment is performed at a temperature of 230° C. for 13 hours, the heat treatment method is drying under constant temperature and humidity conditions, wherein the relative humidity is 30%, to obtain a highly scratch-resistant and wear-resistant coating material; Wherein, the preparation of acrylate-modified polysilazane comprises the following steps: S1. Dissolve 7 parts of 3-(trimethyloxysilyl)propyl methacrylate and 0.15 parts of dimethylaminopyridine in isopropanol according to weight, and adjust the pH value to 4-6 to obtain an acrylate mixture; S2. Dissolve 6 parts of polysilazane in cyclohexane according to weight to obtain a polysilazane mixed solution, add the acrylate mixed solution dropwise to the polysilazane mixed solution at a rate of 4 drops / second, mix evenly, remove the organic solvent after the reaction, add 0.2 parts of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, and obtain acrylate-modified polysilazane; The preparation of modified nano-tungsten carbide includes the following steps: A1. Ultrasonic dispersion of nano-tungsten carbide in a mixed solution of anhydrous ethanol and deionized water in a mass ratio of 8.5:1, and adding N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane under stirring, raising the temperature to 75°C, constant temperature magnetic stirring for 7 hours, centrifugation, washing, and drying to obtain organosilicon-modified nano-tungsten carbide; A2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4 hours, and dried and ground after the reaction is completed; A3. The graphene pretreated in step A2 is added to ethanol for ultrasonic dispersion, and the organosilicon-modified nano-tungsten carbide prepared in step A1 is added, and the mixture is rapidly stirred at 30°C for full reaction, centrifuged, washed several times with anhydrous ethanol, and then vacuum dried, and ground to obtain modified nano-tungsten carbide; In step A1, the weight ratio of the nano-tungsten carbide, the anhydrous ethanol and the N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane is 1:9:0.2.

[0050] Comparative Example 3 Preparation of highly scratch-resistant and wear-resistant coating materials: Select the following raw materials by weight: 25 parts of tetraphenol ethane tetraglycidyl ether epoxy resin, 20 parts of polyurethane-modified polytetrafluoroethylene, 20 parts of acrylate-modified polysilazane, 10 parts of modified nano-tungsten carbide, 4 parts of curing agent, 2 parts of dispersant, and 0.8 parts of 2,6-di-tert-butyl-p-cresol; wherein the dispersant includes carbamate and polycarboxylate ether, and the curing agent is a mixture of triethylenetetramine and hydroxyalkylamide curing agent in a weight ratio of 1.5:1; (1) tetraphenol ethane tetraglycidyl ether epoxy resin, polyurethane modified polytetrafluoroethylene, acrylate modified polysilazane, modified nano tungsten carbide and dispersant were stirred and mixed according to weight parts for 4 minutes at a stirring temperature of 20° C. to obtain a mixed raw material; (2) Adding the curing agent to the mixed raw materials according to the weight portion and stirring for 9 minutes at a stirring temperature of 45° C. to obtain a mixed coating; (3) Adding 2,6-di-tert-butyl-p-cresol into the mixed coating according to parts by weight and stirring for 6 minutes at a stirring temperature of 20° C. to obtain an antioxidant coating; (4) applying the antioxidant coating to the surface of the metal substrate, and heat treating the metal substrate at 230° C. for 13 h, wherein the heat treatment is carried out by drying the metal substrate under constant temperature and humidity conditions, wherein the relative humidity is 30%, to obtain a highly scratch-resistant and wear-resistant coating material; The preparation method of polyurethane modified polytetrafluoroethylene is as follows: dehydrate 10 parts of trihydroxy polyoxypropyl ether by weight at a temperature of 110°C and a vacuum degree of -0.1MPa for 1.5 hours; cool to 70°C, add 7 parts of hexamethylene diisocyanate, and react at 80°C for 1.8 hours to synthesize a prepolymer; add 8 parts of polytetrafluoroethylene, 0.03 parts of dibutyltin dilaurate, 2.5 parts of 4,4'-methylenebis(2-chloroaniline), and 12 parts of a solvent, heat to 115°C and mix evenly to obtain polyurethane modified polytetrafluoroethylene; The solvent is a mixture of methyl butyl ketone and toluene in a weight ratio of 1:1.5; The preparation of acrylate-modified polysilazane comprises the following steps: S1. Dissolve 7 parts of 3-(trimethyloxysilyl)propyl methacrylate and 0.15 parts of dimethylaminopyridine in isopropanol according to weight, and adjust the pH value to 4-6 to obtain an acrylate mixture; S2. Dissolve 6 parts of polysilazane in cyclohexane according to weight to obtain a polysilazane mixed solution, add the acrylate mixed solution dropwise to the polysilazane mixed solution at a rate of 4 drops / second, mix evenly, remove the organic solvent after the reaction, add 0.2 parts of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, and obtain acrylate-modified polysilazane; The preparation of modified nano-tungsten carbide includes the following steps: A1. Ultrasonic dispersion of nano-tungsten carbide in a mixed solution of anhydrous ethanol and deionized water in a mass ratio of 8.5:1, and adding N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane under stirring, raising the temperature to 75°C, constant temperature magnetic stirring for 7 hours, centrifugation, washing, and drying to obtain organosilicon-modified nano-tungsten carbide; A2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4 hours, and dried and ground after the reaction is completed; A3. The graphene pretreated in step A2 is added to ethanol for ultrasonic dispersion, and the organosilicon-modified nano-tungsten carbide prepared in step A1 is added, and the mixture is rapidly stirred at 30°C for full reaction, centrifuged, washed several times with anhydrous ethanol, and then vacuum dried, and ground to obtain modified nano-tungsten carbide; In step A1, the weight ratio of the nano-tungsten carbide, the anhydrous ethanol and the N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane is 1:9:0.2.

[0051] The relevant properties of the highly scratch-resistant and wear-resistant coating materials prepared in Examples 1-4 and Comparative Examples 1-3 were tested, and the testing method was as follows: Pencil hardness is tested according to GB / T 6739-2022; Adhesion is tested according to the standard of GB / T 9286-2021, with 0-5 levels representing the adhesion to the substrate, 0 being the best and 5 being the worst; The wear resistance is tested according to GB / T 5478-2008; The corrosion resistance is tested according to the standard of GB / T 9274-1988, with high and low temperature cycle temperature of -20℃ and 180℃, concentrated sulfuric acid test: concentrated sulfuric acid (70wt%), soak for 7 days, observe the corrosion phenomenon; concentrated nitric acid test: concentrated nitric acid (68wt%), soak for 7 days, observe the corrosion phenomenon.

[0052] Performance test data is shown in Table 1 below: Table 1

[0053] It can be seen from Table 1 that the high scratch resistance and wear resistance coating materials prepared in Examples 1-4 of the present application have good performance. With the mutual matching of specific raw material ratios, the hardness, adhesion, wear resistance and corrosion resistance of the prepared coatings can reach a relatively high level.

[0054] Ordinary polysilazane is used in the raw materials of Comparative Example 1, and the rest are the same as in Example 1. The hardness, adhesion, wear resistance and corrosion resistance of the prepared coating material are significantly reduced, which is obviously not as good as the coating materials prepared in Examples 1-4 of the present application, indicating that the use of acrylate-modified polysilazane is very important for the high scratch resistance and wear resistance coating material in the present application. Polysilazane has good high temperature resistance and corrosion resistance, can maintain stable performance under high temperature environment, does not decompose or fall off, and the corrosion resistance and weather resistance of the polysilazane modified by acrylate are further improved, which can adapt to more environments, and at the same time improve the bonding strength with the metal substrate and other raw materials, thereby improving the stability of the coating material in different environments.

[0055] Ordinary polytetrafluoroethylene is used as the raw material of Comparative Example 2, and the rest are the same as Example 1. The hardness, adhesion, wear resistance and corrosion resistance of the prepared coating material are significantly reduced, which is obviously inferior to the coating materials prepared in Examples 1-4 of the present application, indicating that the use of polyurethane-modified polytetrafluoroethylene is very important for the high scratch-resistant and wear-resistant coating materials in the present application. Polytetrafluoroethylene has good wear resistance and excellent chemical stability. The elasticity and adhesion of polyurethane and the good wear resistance and high and low temperature resistance of polytetrafluoroethylene are combined by polyurethane-modified polytetrafluoroethylene. The polyurethane-modified polytetrafluoroethylene not only has excellent wear resistance and high and low temperature resistance, but also has good elasticity and adhesion, and can maintain stability and is not easy to fall off when subjected to external force impact.

[0056] In step (4) of the preparation method of comparative example 3, no drying treatment is performed, and the rest is the same as that of example 1. The hardness, adhesion, wear resistance and corrosion resistance of the prepared coating material are significantly reduced, and are obviously inferior to the coating materials prepared in examples 1-4 of the present application. This shows that the preparation steps in the present application are very important for preparing highly scratch-resistant and wear-resistant coating materials. The present application performs a drying treatment in advance, which helps to absorb the organic solvent in the antioxidant coating, thereby reducing the particle agglomeration phenomenon caused by the surface tension of the organic solvent inside the coating, thereby making the raw material dispersion more uniform; drying causes the cross-linking between the resins to proceed gradually, which has a certain effect on the hardness and scratch resistance of the prepared coating.

[0057] Although the embodiments of the present application have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions or variations may be made to the embodiments without departing from the principles and purpose of the present application, and that the technical solutions after these changes, modifications, substitutions or variations will fall within the scope of protection of the present application.

Claims

1. A highly scratch-resistant and wear-resistant coating material, characterized in that: The preparation comprises the following raw materials in parts by weight: 20-30 parts of tetraphenol ethane tetraglycidyl ether epoxy resin, 15-25 parts of polyurethane modified polytetrafluoroethylene, 15-25 parts of acrylate modified polysilazane, 5-15 parts of modified nano tungsten carbide, 2-5 parts of curing agent, 1-3 parts of dispersant, 0.5-1 parts of antioxidant; The preparation of the polyurethane-modified polytetrafluoroethylene comprises the following steps: According to weight, 8-12 parts of trihydroxy polyoxypropyl ether are dehydrated at a temperature of 100-120°C and a vacuum degree of -0.1MPa for 1-2h; the temperature is lowered to 60-80°C, 6-8 parts of hexamethylene diisocyanate are added, and the prepolymer is reacted at 78-82°C for 1.5-2h to synthesize the prepolymer; 5-10 parts of polytetrafluoroethylene, 0.02-0.04 parts of catalyst, 2-3 parts of 4,4'-methylenebis(2-chloroaniline), and 8-15 parts of solvent are added, and the mixture is heated to 110-120°C and mixed evenly to obtain polyurethane-modified polytetrafluoroethylene.

2. The highly scratch-resistant and wear-resistant coating material according to claim 1, characterized in that: The preparation of the acrylate-modified polysilazane comprises the following steps: S1. Dissolve 6-8 parts of 3-(trimethyloxysilyl)propyl methacrylate and 0.1-0.2 parts of dimethylaminopyridine in an organic solvent according to weight parts, and adjust the pH value to 4-6 to obtain an acrylate mixture; S2. Dissolve 5-6 parts of polysilazane in an organic solvent according to weight to obtain a polysilazane mixed solution, add the acrylate mixed solution dropwise to the polysilazane mixed solution at a rate of 1-6 drops / second, mix well, remove the organic solvent after the reaction, add 0.1-0.2 parts of a photoinitiator, and obtain acrylate-modified polysilazane.

3. The highly scratch-resistant and wear-resistant coating material according to claim 2, characterized in that: In step S2, the photoinitiator is selected from at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, (2,4,6-trimethylbenzoyl)diphenylphosphine oxide and 2-isopropylthioxanthone.

4. The highly scratch-resistant and wear-resistant coating material according to claim 1, characterized in that: The preparation of the modified nano-tungsten carbide comprises the following steps: A1. Ultrasonic dispersion of nano-tungsten carbide in a mixed solution of anhydrous ethanol and deionized water (8-9):1 by mass ratio, and adding N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane under stirring, raising the temperature to 70-80°C, constant temperature magnetic stirring for 5-8h, centrifugation, washing, and drying to obtain organosilicon-modified nano-tungsten carbide; A2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4 hours, and dried and ground after the reaction is completed; A3. Add the graphene pretreated in step A2 to ethanol for ultrasonic dispersion, add the organosilicon-modified nano-tungsten carbide prepared in step A1, stir rapidly at 25-35°C to allow it to react fully, centrifuge, wash several times with anhydrous ethanol, dry in vacuum, and grind to obtain modified nano-tungsten carbide.

5. The highly scratch-resistant and wear-resistant coating material according to claim 4, characterized in that: In step A1, the weight ratio of the nano-tungsten carbide, the anhydrous ethanol and the N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane is 1:(8-10):(0.1-0.2).

6. The highly scratch-resistant and wear-resistant coating material according to claim 1, characterized in that: The dispersants include urethanes and polycarboxylate ethers.

7. The highly scratch-resistant and wear-resistant coating material according to claim 1, characterized in that: The curing agent is prepared by mixing triethylenetetramine and hydroxyalkylamide curing agent in a weight ratio of (1-2):

1.

8. The highly scratch-resistant and wear-resistant coating material according to claim 1, characterized in that: The antioxidant is selected from at least one of 2,6-di-tert-butyl-p-cresol, tert-butylhydroquinone, butylated hydroxyanisole, hydroquinone or o-methylhydroquinone.

9. A method for preparing a highly scratch-resistant and wear-resistant coating material according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Tetraphenol ethane tetraglycidyl ether epoxy resin, polyurethane modified polytetrafluoroethylene, acrylate modified polysilazane, modified nano tungsten carbide and dispersant are stirred and mixed according to weight parts for 3-4 minutes at a stirring temperature of 15-25° C. to obtain a mixed raw material; (2) Add the curing agent to the mixed raw materials according to the weight portion and stir for 8-10 minutes at a stirring temperature of 40-50° C. to obtain a mixed coating; (3) adding an antioxidant to the mixed coating according to parts by weight and stirring for 5-6 minutes at a stirring temperature of 15-25° C. to obtain an antioxidant coating; (4) The antioxidant coating is applied to the surface of a metal substrate, first dried, and then heat treated to obtain a highly scratch-resistant and wear-resistant coating material.

10. The method for preparing a highly scratch-resistant and wear-resistant coating material according to claim 9, characterized in that: The drying in step (4) includes pre-drying and post-drying; the pre-drying temperature is 115-140°C; the pre-drying time is 20-30min; the post-drying temperature is 150-170°C; the post-drying time is 25-35min; the drying method in step (4) is hot air drying; the heat treatment temperature in step (4) is 210-240°C; the heat treatment time in step (4) is 10-15h; the heat treatment method in step (4) is drying under constant temperature and humidity conditions, wherein the relative humidity is 25%-35%.

Citation Information

Cited By

  • Manufacturing method of convenient dual-purpose microcellular foaming mold

    CN120484637A

  • Ash sticking prevention carbon nano polymer coating as well as preparation method and application thereof

    CN121160182A